(untitled) (Herald of Journalism, 2021)
We tried to study reality shows on domestic television, to determine the observance of moral and ethical principles and its impact on society. The purpose is to consider reality shows in Kazakhstan that have not yet formed in terms of genre. Moreover, we have to scrutinize the adherence of ethical and legal norms in broadcasting programs in this area and its influence on society. The idea is to consider the issues and prospects of private reality shows. Also, identify efficient models of this form for our television from the world experience of this form. Scientific and practical significance – there is a negative opinion in society that a reality show is a way to keep its audience in front of the screen by arguing, broadcasting immoral actions. The explorational work implicates forming of a stable mentality that will change the unequal assumption of many regarding reality TV. As the research methodology used in the methods of analysis, comparison, generalization, review study. The expected result is to confirm the genre features of reality shows on television applying specific examples; to cite an example of a television project in the form of an unconventional reality show, which has not yet found reflection on domestic television. The value of the research: The article is basing on the scientific works of domestic and foreign experts. Furthermore, were viewed internet resources as individual television channel websites. Statistical data from the television informational organizations specifically evaluated to disclose the essence of the work. For this, were analyzed about 50 reality-show programs from domestic and several foreign channels. Today, there are several scientific works of world media analysts about reality-show in television. However, the materials provided by Kazakhstani television journalism do not provide complete information about this form. Actually, besides published comments of irrespective specialists and television veterans on the mass media, there is not significant explorational data about this form. Consequently, the information there can be used to monitor the progress degree of the reality-show. Keywords: reality-show, television genre, society, journalism ethics